Preaching the headlines : possibilities and pitfalls - Thompson, Lisa L. (Working Preacher., 2021)
Preaching the Headlines reframes preaching as an ongoing conversation between the modern world and the world of the biblical text. Preachers use what they know about life as a bridge to the text, while life in the text provides the bridge back to faith in the contemporary world. The goal of the book is to provide a process to aid preachers in doing theological reflection on the everyday world as an integral part of sermon development.